Serum CCL 18 Levels in Women with Polycystic Ovarian Syndrome - Sam, Justin Easow (Indian J Endocrinol Metab, 2020)
BACKGROUND: Polycystic ovarian syndrome (PCOS) is one of the most common metabolic disorders seen in women of the reproductive age group, with the majority of them having insulin resistance. There is a need to identify sensitive markers of insulin resistance. CC chemokine ligand 18 (CCL 18) secreted from white adipose tissue is upregulated in individuals with insulin resistance. OBJECTIVES: To study the correlation between serum CCL 18 levels and insulin resistance in PCOS. MATERIALS AND METHODS: This case-control study included 45 PCOS women and an equal number of age and body mass index (BMI) matched controls. Estimation of serum CCL 18, serum testosterone, fasting plasma glucose, fasting insulin, HbA1c, and ultrasonography of abdomen and pelvis was done and HOMA IR was calculated. RESULTS: Serum CCL 18 level was higher in women with PCOS when compared to controls. The mean level of serum CCL 18 (ng/mL) in the PCOS group and control group was 28.32 ± 4.17 and 11.90 ± 4.91, respectively (P < 0.001). Blood pressure, waist circumference, waist-hip ratio, modified Ferriman Gallway score (FG) score serum total testosterone, fasting serum insulin, and HOMA IR showed a relationship with serum CCL 18 levels. Serum CCL 18 was an independent predictor of PCOS (P < 0.05). A serum CCL 18 cutoff level of 18.84 ng/mL showed 93.3% sensitivity and 91.7% specificity in distinguishing PCOS subjects from healthy individuals. CONCLUSION: There is a significant correlation of serum CCL 18 level with insulin resistance in PCOS subjects and serum CCL levels can be considered as a marker of PCOS.